Fahrs Disease: A Rare Neurodegenerative Disorder in Children - Rahman, AKM Matiur; Begum, Rashida Sadia; Anwar, Sayeeda; Ali, Md Ramzan; Rahman, Mowshumi (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v35i3.10524 Bangladesh J Child Health 2011; Vol 35 (3): 121-123